2013
DOI: 10.1021/jo402101h
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Enantioselectivity of Dirhodium-Catalyzed Intramolecular C–H Amination of Sulfamate

Abstract: The mechanisms and enantioselectivities of the dirhodium (Rh2L4, L = formate, N-methylformamide, S-nap)-catalyzed intramolecular C-H aminations of 3-phenylpropylsulfamate ester have been investigated in detail with BPW91 density functional theory computations. The reactions catalyzed by the Rh2(II,II) catalysts start from the oxidation of the Rh2(II,II) dimer to a triplet mixed-valent Rh2(II,III)-nitrene radical, which should facilitate radical H-atom abstraction. However, in the Rh2(formate)4-promoted reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 76 publications
2
28
0
Order By: Relevance
“…With rhodium( ii ) dimer complexes, such as Rh 2 (OAc) 4 , using carbamate- and sulfamate-derived iminoiodinane reagents, a concerted asynchronous insertion of a singlet Rh( ii )–nitrene has been found in previous computational studies,59,60 in agreement with what was observed experimentally 33,58,61. For Rh 2 (esp) 2 , an alternative one-electron mechanism involving Rh( ii )–Rh( iii ) intermediates has been proposed with a concerted C–H insertion step 6264. Conversely, computational and experimental data have established a stepwise mechanism for the C–H amination catalyzed by a diruthenium complex involving a short-lived diradical species 23,65…”
Section: Introductionsupporting
confidence: 84%
“…With rhodium( ii ) dimer complexes, such as Rh 2 (OAc) 4 , using carbamate- and sulfamate-derived iminoiodinane reagents, a concerted asynchronous insertion of a singlet Rh( ii )–nitrene has been found in previous computational studies,59,60 in agreement with what was observed experimentally 33,58,61. For Rh 2 (esp) 2 , an alternative one-electron mechanism involving Rh( ii )–Rh( iii ) intermediates has been proposed with a concerted C–H insertion step 6264. Conversely, computational and experimental data have established a stepwise mechanism for the C–H amination catalyzed by a diruthenium complex involving a short-lived diradical species 23,65…”
Section: Introductionsupporting
confidence: 84%
“…Conversely, the S−O(R) bond inclines parallel to the metal plane in the Lie‐mode. Our previous work and an investigation of Du Bois and co‐workers found that the Stand‐mode of the transition states of the hydrogen abstraction appears preferable and thereby, only the Stand‐mode will be further considered.…”
Section: Resultsmentioning
confidence: 99%
“…With the development of theoretical methods and the diversity of chemical means, DFT has become an important tool for comprehending the mechanisms of chemical reactions, and numerous theoretical studies on rhodium‐catalyzed reactions have come to our attention. Zhao and co‐workers explained that the preferential mechanism of [Rh 2 ( S‐ nap) 4 ]‐catalyzed [nap = N‐(2‐hydroxypiperidin‐3‐yl)‐4‐methylbenzenesulfonamide] C–H amination reactions mainly relies on the electronic effect of catalyst ligands. Qu and Cramer reported C–H activation and illustrated the importance of the catalyst ligand in Rh‐based systems.…”
Section: Introductionmentioning
confidence: 99%